The Validity and Reliability of a Smartphone Application for Break-Point Angle Measurement during Nordic Hamstring Exercise - Toshiaki Soga; Shota Yamaguchi; Takayuki Inami; Hiromi Saito; Nadaka Hakariya; Naoto Nakaichi; Sho Shinohara; Kei Akiyama; Norikazu Hirose (International Journal of Sports Physical Therapy)
# Background